Tenofovir alafenamide versus entecavir for treating hepatitis B virus-related acute-on-chronic liver failure: real-world study - Peng, Wenting; Gu, Huimin; Cheng, Da; Chen, Keyu; Wu, Cichun; Jiang, Chuan; Liu, Jinqing; Peng, Shifang; Fu, Lei (Frontiers in Microbiology, 2023)
Background and Aims: Real-world data regarding hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) patients receiving tenofovir alafenamide (TAF) as an antiviral drug are limited. Hence, we evaluated the efficacy and kidney safety of TAF among this population. Methods: A total of 272 HBV-related ACLF patients hospitalized at Xiangya Hospital of Central South University were enrolled in this retrospective research. All patients received antiviral therapy with TAF (n=100) or ETV (n=172) and complex treatments. Results: Through 1:1 propensity score matching, 100 patients were finally included in each group. At week 48, the survival rates without transplantation of the TAF group and ETV group were 76.00% and 58.00%, separately (P=0.007). After 4 weeks of treatment, the TAF treatment group exhibited a significantly decline in HBV DNA viral load (P=0.029). The mean estimated glomerular filtration rate was apparently improved in the TAF group compared with the ETV group (TAF 5.98 ± 14.46 vs. ETV 1.18 ± 18.07 ml/min/1.73 m2) (P<0.05). There were 6 patients in TAF group and 21 patients in ETV group with chronic kidney disease (CKD) stage progression≥1. By contrast, the ETV treatment group has a greater risk of renal function progression in CKD 1 stage patients (P<0.05). Conclusions: This real-world clinical study showed that TAF is more effective than ETV in reducing viral load and improving survival rate in HBV-ACLF patients and the risk of renal function decline is lower.